Side by Side: Reflections on Two Lifetimes of Dance - Kipling Brown, Ann; Penniston Gray, Anne (Frontiers in Psychology, 2021)
Telling stories about our experiences in dance brings to light unconscious knowledge and memories of the past and helps us understand our own decisions and practices. Reflexivity and story telling is central in the process of remembering and embodies some of the key aspects of narrative as a research tool. We are directed to examine and reflect on our experiences, analyzing goals and intentions, making connections between happenings and recounting the personal meanings of an experience. Dance has the potential for positive impact on both physical and mental health among professional dancers as well as among dance students and has the power to connect them to culture and community in unique and important ways. Research has provided evidence that arts engagement provides positive forms of social inclusion, opportunities to share arts, culture, language and values and points to the value of the arts in the prevention and amelioration of health problems. Together with those benefits of a dance experience there is clear evidence of what can be learned in, through and about dance. In this time of the Covid-19 pandemic it seemed more relevant and poignant to examine those past experiences that had influenced our lives as well as many others.